2020
DOI: 10.1093/jac/dkaa368
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics and dosing simulations of amoxicillin in obese adults receiving co-amoxiclav

Abstract: Background Pneumonia, skin and soft tissue infections are more frequent in obese patients and are most often treated by co-amoxiclav, using similar dosing regimens to those used for non-obese subjects. No data are available on amoxicillin pharmacokinetics among obese subjects receiving co-amoxiclav. Materials and methods Prospective, single-centre, open-label, non-randomized, crossover pharmacokinetic trial having enrolled ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…Co-amoxiclav (Augmentin) is a combination of clavulanic acid and amoxicillin [ 2 , 10 , 13 ]. The addition of clavulanic acid broadens the antibacterial spectrum of amoxicillin to include the bacteria which produce beta lactamase enzyme [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Co-amoxiclav (Augmentin) is a combination of clavulanic acid and amoxicillin [ 2 , 10 , 13 ]. The addition of clavulanic acid broadens the antibacterial spectrum of amoxicillin to include the bacteria which produce beta lactamase enzyme [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The co-amoxiclav used in this study is bactericidal instead of bacteriostatic. Oral administration of 625 mg co-amoxiclav requires 1.5 h to reach its peak blood concentration [ 10 ]. However, it may take up to 48 h of dosing for clinical improvement to appear [ 1 , 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mellon et al, observed that the amoxicillin C max decreased significantly with weight. Considering the target PK/PD value for beta-lactams fT > MIC ≥ 40%, the standard dosage of co-amoxiclav (1000/125 mg every 8 h) should be efficacious for obese adults [22], but Soares et al, suggested that amoxicillin treatment would fail if standard therapeutic regimens were applied because of a significantly higher volume of distribution in this group of patients [23].…”
Section: Stagementioning
confidence: 99%